An Amplitude-Integrated EEG Evaluation of Neonatal Opioid Withdrawal Syndrome - Lust, Christopher; Vesoulis, Zachary; Zempel, John; Gu, Hongjie; Lee, Stephanie; Rao, Rakesh; Mathur, Amit M. (American Journal of Perinatology, 2022)
Objective Infants with neonatal opioid withdrawal syndrome (NOWS) have disrupted neurobehavior that requires hospitalization and treatment. This article aimed to evaluate electroencephalography (EEG) abnormalities using amplitude-integrated EEG (aEEG) in NOWS.Study Design Eighteen term born infants with NOWS were recruited prospectively for an observational pilot study. aEEG monitoring was started within 24 hours of recruitment and twice weekly through discharge. aEEG data were analyzed for background and seizures. Severity of withdrawal was monitored using the modified Finnegan scoring (MFS) system.Results Fifteen neonates had complete datasets. Thirteen (87%) had continuous aEEG background in all recordings. None had sleep–wake cyclicity (SWC) at initial recording. Brief seizures were noted in 9 of 15 (60%) infants. Lack of SWC was associated with higher MFS scores. At discharge, 8 of 15 (53%) had absent or emerging SWC.Conclusion aEEG abnormalities (absent SWC) are frequent and persist despite treatment at the time of discharge in the majority of patients with NOWS. Brief electrographic seizures are common. Neonates with persistent aEEG abnormalities at discharge warrant close follow-up.Key Points
Keywords: amplitude-integrated EEG; neonatal opioid withdrawal syndrome; neonatal sleep–wake cyclicity; neonatal seizures; modified Finnegan score